Effect of Diet Type and Population Density on the Biology of Samia cynthia ricini Boisduval (Lepidoptera: Saturniidae) - Nurkomar, Ihsan; Dina Wahyu Trisnawati; Ibnu Fadillah Ramadhan (Andalasian International Journal of Entomology, 2025)
The silkworm is an insect with high economic value due to its ability to produce cocoons, which are processed into silk fibers. Samia cynthia ricini is a type of silkworm relatively new to Indonesia. This insect can utilize various plants as feed, with castor leaves as the primary host and cassava leaves as the secondary host. However, information regarding the impact of diet type and population density on biological parameters, such as survival rate, development time, cocoon weight, and fecundity, remains limited. This study aims to evaluate the effects of diet type (castor and cassava leaves) and population density (20, 30, 40, and 50 individuals per container) on the biology of S. c. ricini. The research used a factorial randomized complete block design (RCBD) with two factors. Results indicated that diet type and population density significantly influenced the biological parameters of S. c. ricini. Silkworms fed castor leaves exhibited higher survival rates and heavier cocoon weights than those fed cassava leaves. Increased population density reduced survival rates, cocoon weights, and fecundity. The optimal population density for rearing was 30 individuals per container. These findings provide valuable insights for improving S. c. ricini rearing practices. Using castor leaves as the primary diet and maintaining an optimal population density of 30 individuals per container can enhance survival and cocoon quality. This information is particularly useful for small-scale and laboratory rearing efforts, contributing to the sustainable development of S. c. ricini cultivation and silk production.